RESPONS TANAMAN SAWI (Brassica juncea L.) TERHADAP PUPUK ANORGANIK dan PUPUK ORGANIK BAHAN DASAR GULMA - Claudia Yudiarti Rahalus; Pemmy Tumewu; Antje Grace Tulungen (COCOS, 2019)
ABSTRACT Mustard is one of the agricultural products that interests the community, so it has high commercial potential and value. The use of organic fertilizers in the soil can improve soil properties (physical, chemical and biological properties). This research uses weed as a basic material in making organic fertilizer and inorganic fertilizer. This study aims to determine the effect of inorganic fertilizers and organic fertilizers as well as the single effect of the two fertilizers on the growth and yield of mustard as well as a good dose for mustard plants. The research was carried out in the experimental garden of the Faculty of Agriculture, Sam Ratulangi University, Walian Village, Tomohon City, in August until October 2018 and the Mapanget Balitpalma Laboratory. The experiment used a completely randomized design factorial pattern. The first factor (A) = Fertilizer consists of A0 = 0 kg Phonska / ha and 0 kg Urea / ha, A1 = 200 kg Phonska / ha and 100 kg Urea / ha. The second factor (B) = Organic weed fertilizer (Paitan, Arakan, Kirinyuh) consisting of: B1 = 15 tons of weed / ha organic fertilizer, B2 = 20 tons of weed / ha organic fertilizer, B3 = 25 tons of weed organic fertilizer / ha and B4 = 30 tons of weed / ha organic fertilizer. Every 8 treatments were repeated 3 times to obtain 24 experimental pots. The results showed that there were interactions between inorganic and organic fertilizers on plant wet weight at a dose of A1B1 (200kg Phonska / ha, 100kg Urea / ha and 15 tons of weed organic fertilizer). The results showed that the application of inorganic fertilizers and organic fertilizer as a basis for weeds provided good wet weight of mustard plants. A good dose of fertilizer for mustard cultivation can use 200 kg Phonska / ha, 100kg urea / ha and 15 tons / ha organic fertilizer. Keywords: Mustard, Inorganic Fertilizer, Organic Fertilizer, Weed